The geologic potentials of Riau Islands Province and its development design - Emi Sukiyah; Vijaya Isnaniawardhani; Adjat Sudradjat; Fery Erawan (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2018)
Geologically Riau Islands is located in the topography of the old stadium erosion. The morphology is characterized by smooth hills with convex slopes and alluvial plain consisting of the erosion products. The morphology exhibits the remnants of peneplain that submerged at ca 13,000 BP now forming Sunda Shelf with the average depth of 120 meters. The irregular coast’s line of almost all the islands in Riau Islands characterized the submerged old morphologic stadium. The lithology consists of granites and metasediments. Granites contain various types of economic minerals. The weathered granites produce bauxite, kaolin and quartz sands. The metasediments are generally soft resulting in the formation of valleys suitable for agriculture and settlements due to the availability of surface and subsurface water. Irregular coastal line provides the bays for harbors. The geological potentials to be developed therefore consists of the provision of stable plain and resistance to landslide and earthquake, the bays suitable for various marine industries, granites for building materials, and base metals. The submarine hydrocarbon basins produce oil and gas. Geologically Riau Islands is very unique because it represents the remnants of the peneplain of Jurassic and Cretaceous age of about 63 to 181 years old now becoming the Sunda shelf which is the largest in the world. This region is very good when developed as an industrial area, trade, and marine tourism Keywords: Riau Islands, geologic potentials, granites, submerge, marine tourism